The contingency of voter learning: how election debates influence voters’ ability and accuracy to position parties in the 2010 Dutch election campaign - Van der Meer, Tom W.G.; Walter, Annemarie; Van Aelst, Peter (Taylor & Francis, 2015)
Election campaigns are expected to inform voters about parties’ issue positions, thereby increasing voters’ ability to influence future policy and thus enhancing the practice of democratic government. We argue that campaign learning is not only contingent on voters’ characteristics and different sources of information, but also on how parties communicate their issue positions in election debates. We combine a two-wave panel survey with content analysis data of three televised election debates. In cross-classified multilevel auto-regression models we examine the influence of these debates in the 2010 Dutch parliamentary election campaign on voters’ knowledge of the positions of eight parties on three issues. The Dutch multiparty system allows us to separate voters’ ability to position parties from their accuracy in ordering these parties. We reach three main conclusions. First, this study shows that voters become more able and accurate during the campaign. However, these campaign learning effects erode after the elections. Second, whereas voters’ attention to campaigns consistently contributes to their ability to position parties, its effect on accuracy is somewhat less consistent. Third, televised election debates contribute to what voters learn. Parties that advocate their issue positions in the debates stimulate debate viewers’ ability to position these parties on these issues. In the face of the complexity of campaigns and debates in multiparty systems, campaigns are more likely to boost voters’ subjective ability to position parties than their accuracy.